Revitalisasi Pendidikan Berbasis Keunggulan Lokal Dalam Bingkai KTSP - Anung Priambodo (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2018)
Abstract: Indonesia's biodiversity and all the other potentials that are fairly abundant must be utilized to improve the welfare of the people. One mechanism that is expected to be able transform potential into aktus is education. Through the Ministry of National Education, the government sought the implementation level of the education curriculum (SBC) to connect the implementation of local excellence as part of the curriculum in school. Local advantages can be put in the subjects of local content (Muatan lokal) or integrated with other subjects. It is expected that learners can identify and develop potential advantages in the area to be objects that benefit for society. Keywords: revitalization, local advantages, and KTSP